Pengaruh Tampilan Produk Dan Gratis Ongkir Terhadap Pembelian Impulsif Produk Fashion Dengan Diskon Sebagai Variabel Moderating (Studi Kasus : Mahasiswa Program Studi Ekonomi Islam Universitas Islam Negeri Sumatera Utara) - Andriani, Fadilah; Bi Rahmani, Nur Ahmadi; Aslami, Nuri (Universitas Labuhanbatu, 2022)
This study aims to find out (1) does product appearance affect the impulsive buying of fashion products (2) does free shipping affect the impulsive buying of fashion products (3) whether discounts can be a moderating variable in the effect of product appearance on impulsive buying of fashion products (4) whether Discounts can be a moderating variable for the effect of free shipping on impulse buying of fashion products. The type of research used is quantitative. The population in this study were active students of the 2018 Islamic Economics study program. The sampling technique used was purposive sampling with a total sample of 73 respondents. Data collection techniques using a questionnaire (questionnaire). The data analysis technique in this study used the interaction test or MRA with the help of SPSS 22 software. The results showed that first, product appearance had no significant effect on impulsive buying of fashion products with a significance value of 0.720 > 0.05. Second, free shipping has a significant effect on impulsive buying of fashion products with a significance value of 0.006 <0.05. Third, the interaction between product displays and discounts has no significant effect on impulse buying of fashion products. That is, discounts are not able to moderate the effect of product appearance on impulse buying of fashion products with a significance value of 0.889 > 0.05. Fourth, the interaction between free shipping and discounts has a positive and significant effect on impulse buying of fashion products. That is, discounts are able to moderate and strengthen the effect of free shipping on impulse buying of fashion products with a significance value of 0.001 <0.05.